НАПРЯМИ РЕФОРМУВАННЯ ДОСУДОВОГО РОЗСЛІДУВАННЯ В УКРАЇНІ - Михайлюк, Артем Миколайович (SUPREMANCE OF LAW, 2018)
Article is devoted to research directions for reforming the pretrial investigation through study historical features of development of an investigator in Ukraine. The article focuses on the problems of pre-trial investigation, which are connected with the presence of controversial powers in the investigator and affect the appointment of a criminal process adversely. On the basis of analysis of the drawback of the national pre-trial investigation formed proposals for further improvement of pre-trial investigation in Ukraine.